Energetic Performance Analysis of Geothermal Heat Exchanger Under Saharan Climate - حاتم, خوازم; سمير, بلول; شهاب, فرحات (University Of El Oued, 2020)
This project presents an experimental analysis to examine the performance of earth to air heat exchanger (EAHE) for cooling building. This system has never been used or exploited in the EL Oued region. Therefore, an experimental system was designed, installed and tested under 3m depth and 45 m of length. The experiments are conducted between 21th and 23th June 2020. The results obtained show that the EAHE system can be used in the homes and poultry and greenhouses for cooling and heating. During the experimental period, the maximum average temperature difference between the inlet and outlet EAHE system is approximately 20 °C, with a measured air flow rate of 128 m3/s. The EAHE efficiency decreased with the increase of the airflow. The efficiency of heat exchanger was obtained to be 93%, 88% and 85% for the average flow rate value of 92, 128 and 157 m3/s, respectively. According to the obtained results, the EAHE presented in this study may be used for cooling and heating of buildings or greenhouses in southeastern Algeria. يقدم هذا المشروع تحليلًا تجريبيًا لفحص أداء المبادل الحراري الأرضي إلى الهواء (EAHE) لمبنى التبريد. لم يتم استخدام هذا النظام أو استغلاله في منطقة الواد. لذلك ، تم تصميم وتركيب واختبار نظام تجريبي تحت عمق 3 أمتار وطول 45 مترًا. أجريت التجارب بين 21 و 23 يونيو 2020. وأظهرت النتائج التي تم الحصول عليها أن نظام EAHE يمكن استخدامه في المنازل والدواجن والصوبات الزراعية للتبريد والتدفئة. خلال فترة التجربة ، يبلغ الحد الأقصى لمتوسط ​​فرق درجة الحرارة بين نظام EAHE المدخل والمخرج حوالي 20 درجة مئوية ، مع معدل تدفق هواء مُقاس يبلغ 128 متر مكعب / ثانية. انخفضت كفاءة EAHE مع زيادة تدفق الهواء. بلغت كفاءة المبادل الحراري 93٪ و 88٪ و 85٪ لمتوسط ​​قيمة تدفق 92 و 128 و 157 م 3 / ث على التوالي. وفقًا للنتائج التي تم الحصول عليها ، يمكن استخدام EAHE المقدم في هذه الدراسة لتبريد وتدفئة المباني أو الصوبات الزراعية في جنوب شرق الجزائر.
Energies renouvelables en mecanique مذكرة ماستر تخصص
Keywords: geothermal energy, Earth Air Heat Exchanger, heating, cooling, renewable energy.; الطاقة الحرارية الأرضية ، مبادل حرارة الهواء الأرضي ، التدفئة ، التبريد ، الطاقة المتجددة.